Catabolism of 3-Nitrophenol by Ralstonia eutropha JMP 134 - Schenzle, A. (1997)
Ralstonia eutropha JMP 134 utilizes 3-nitrophenol as the sole source of nitrogen, carbon, and energy. The entire catabolic pathway of 3-nitrophenol is chromosomally encoded. An initial NADPH-dependent reduction of 3-nitrophenol was found in cell extracts of strain JMP 134. By use of a partially purified 3-nitrophenol nitroreductase from 3-nitrophenol-grown cells, 3-hydroxylaminophenol was identified as the initial reduction product. Resting cells of R. eutropha JMP 134 metabolized 3-nitrophenol to N-acetylaminohydroquinone under anaerobic conditions. With cell extracts, 3-hydroxylaminophenol was converted into aminohydroquinone. This enzyme-mediated transformation corresponds to the acid-catalyzed Bamberger rearrangement. Enzymatic conversion of the analogous hydroxylaminobenzene yields a mixture of 2- and 4-aminophenol.